Pendidikan Islam Klasik : Model Dan Karakteristik - Surono Surono; Mahfud Ifendi Mahfud Ifendi (Thawalib: Jurnal Kependidikan Islam, 2021)
Talking about classical Islamic education basically cannot be separated from the historical background of the birth and development of Islamic education itself. This is because Islamic education which is now developing is the result of the metamorphosis of previous education. When Islamic education during the time of the Prophet and Khulafa al-Rasyidin emphasized more on the cultivation of faith, sharia, and morals as the basis for fostering the people, classical Islamic education reached its peak during the reign of the Abbasid's which was marked by an openness to foreign cultures and thoughts. Therefore, during the Abbasid era, the scientific tradition developed rapidly and gave birth to many Muslim intellectuals, both concerned with philosophy, religious knowledge (tafsir, fiqh, language), and the realm of education. This period by historians called the golden period (The Golden Age), in which, philosophy, religion, and other sciences, especially education developed rapidly with its unique models and characteristics that distinguish it from previous models and characteristics of education.